Tunkaḥu al-Mar’atu li Arbaʻ: Functional Reception of the Hadith on Soulmate Criteria Among Married Couples in Coastal Sumatra - Yunidos, Yunidos; Wendry, Novizal; Efrinaldi, Efrinaldi (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This research aims to explore how married couples perceive the hadith on soulmate qualifications. According to this hadith, the ideal criteria for a soulmate include wealth, lineage, beauty, and religion, which together contribute to a harmonious family life. The study employs qualitative data analysis, gathering data from various groups: prospective married couples, couples who have been married for 10, 20, and 30 years, as well as divorced couples. Additionally, it utilizes information from lectures by religious counsellors (penyuluh agama). The research shows that the interpretation of the hadith on soulmate qualifications has evolved dynamically since the introduction of Islam in the region in the early 17th century. Religious leaders (tokoh agama) and traditional leaders (tokoh adat), along with religious counsellors, have played a significant role in this transmission. People interpret the hadith in diverse ways. Couples who marry young initially focus on wealth, but as they age, their focus shifts to serenity. Similarly, their focus changes from physical beauty to inner beauty over time. Generally, couples view an ideal mate as someone who can maintain a lasting household, provide offspring, and uphold honour. The findings suggest that couples' understanding of religious texts grows deeper as their marriage matures.